RESIDU BOKASHI KALAKAI DAN PUPUK NPK TERHADAP PERTUMBUHAN DAN HASIL JAGUNG KETAN (Zea mays certain ) PADA LAHAN GAMBAUT PEDALAMAN: Bokashi Kalakai Residue and NPK Fertilizer on Growth and Yield of Glutinous Corn (Zea mays certain) on Peatland - Herlianur Herlianur; Syahrudin Syahrudin; Untung Darung; Kambang Vetrani Asie (Fakultas Pertanian Universitas Palangka Raya, 2022)
The purpose of this research was to know determine the residue of bokashi kalakai with NPK fertilizer on inland peat soil on the growth and yield of glutinous corn (Zea mays certain ) This research was carried out in March 2021-May 2021 in the previous research area, Kalampangan Village, Sebangau District, Palangka Raya, Central Kalimantan Province. The experiment design conduted Randomized Block Dessign with single factor consisting 5 levels of treatment, namely, F0 = Control, F1 = Bokashi Kalakai Residue (15 ) + NPK (200 kg), F2 = Bokashi Kalakai Residue (15 ) + NPK (300 kg), F3 = Bokashi Kalakai Residue (15 ) + NPK (400 kg) dan F4 = Bokashi Kalakai Residue (15 ) + NPK (500 kg). The results showed that the residue of bokashi kalakai 15 t ha-1 + NPK 500 kg ha-1 was able to increase plant height growth of 110.67 cm (7 WAP) , the number of leaves was 7.89 strands ( 7 WAP), stem diameter 1.36 (7 WAP), leaf area 208.25 cm-2 (7 WAP), total dry weight of the plant 10.26 g (7 WAP), plant wet weight 62.97g (7 WAP), fresh weight of 60.98 g (7 WAP) and 132.40 g (7 WAP) fresh weight without husks